Stark raving mad - Baldecchi, John.; Daywalt, Drew.; Schneider, David; Scott, Seann William, 1976-; Breen, Patrick; Chen, Terry; Crye, John.; Foley, Dave, 1963-; Hungerford, Paul.; Mazur, Monet, 1976-; Nakamura, Suzi.; Neis, Reagan Dale, 1976-; et al. (Culver City, California Columbia TriStar Home Entertainment, 2004)
Ben is convinced he has come up with the perfect plan when he arranges a massive rave to cover up a bank heist. Determined to get his brother out of a deadly debt to the mob, Ben assembles a crack team of accomplices and goes to work. Everything should go off without a hitch if the rave stays loud enough, if the team can drill through the wall in time and if no one catches them once they are inside.
Originally released as a motion picture in 2002.
Director of photography, Chuck Cohen ; editor, Hughes Winborne ; music, John Digweed, Nick Muir ; costume designer, Alison Krost ; production designer, Keith Brian Burns.
Seann William Scott, Patrick Breen, Terry Chen, John Crye, Dave Foley, Paul Hungerford, Monet Mazur, Suzi Nakamura, Reagan Dale Neis, Lou Diamond Phillips.
MPAA rating: R; for strong sexual content, language, some drug use and violence.
DVD, widescreen (1.85:1) presentation; Dolby Digital.
English or Spanish dailogue with optional English, Spanish or French subtitles; closed-captioned.
Keywords: Bank robberies -- Drama; Raves (Parties) -- Drama; Accomplices -- Drama; Feature films; Feature films; Video recordings for the hearing impaired; Drama; Suspense films